PENGARUH NILAI OKTAN BAHAN BAKAR DAN PUTARAN MESIN PADA KENDARAAN BERMOTOR TERHADAP KARAKTERISTIK EMISI GAS BUANG - Sastra Negara, I P; Budiarsa Suyasa, I W; Suarna, I W (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
The air pollution that is occurring currently is main by caused by the use of motor vehicle that consequently it lead to the increasing fuel consumptions as the main source enrgy for transportation equipment. The fuel that is used in the vehicle comes in several types. In the market its differences show by the octane numbers that can contribute different effect to the environment due to their combustion processes. The road conditions through which the vehicles move are the major factors that can trigger the growth of pollution to the surrounding. It is predicted that about 70% of the air pollutions is caused by the motor vehicle emissions.This research was fully conducted in the laboratorium. Three types of fuel with different octane numbers were used in this research. Premium with octane number 88, Pertamax with octane number 92, and Biopertamax with octane number 91. The engine speeds were also varied from 500 rpm, 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, to 4000 rpm. For every type of fuel, the engine was run five times for every engine speed in order to obtain the exhausted gas characteristics from the vehicles to the environment.The result of the research shows that at engine speed of 2500 rpm the CO emission for each type of fuel : Premium with octane number 88 is 0,415%, Pertamax with octane number 92 is 0,556%, and Biopertamax with octane number 91 is 0,273%. The octane number also effects the CO2, HC, and NOx emissions in small quantities. Statistical analysis shows both the engine speed and the octane number contribute significant effects on the exhaust emissions, the CO and HC emissions provided negative effects, while the CO2 and NOx emissions get positive effects. In comparisan to with the vehicle speed on the road from secondary data to represent the engine speed in the laboratorium, and assuming that the traffic density is identical to a factor that determining engine speed, it can be concluded that the air pollution by CO emission due to the characteristics of the road has negative influence.The octane number of the fuel and the engine speed gives a significant effect. The traffic density and the road conditions can trigger the level of the concentration of CO gas as pollutants to the surrounding air.
Keywords: Octane number, engine speed, and exhaust gas characteristic.